2020
DOI: 10.3389/fphys.2020.00798
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Long Non-coding RNAs and MicroRNAs in Heart Disease: Insight Into Mechanisms and Therapeutic Approaches

Abstract: Cardiovascular disease is the leading cause of mortality worldwide and there is an increasing need to identify new therapeutic targets that could be used to prevent or treat these diseases. Due to recent scientific advances, non-coding RNAs are widely accepted as important regulators of cellular processes, and the identification of an axis of interaction between long non-coding RNAs (lncRNAs) and micro RNAs (miRNAs) has provided another platform through which cardiovascular disease could be targeted therapeuti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 182 publications
(201 reference statements)
0
22
0
Order By: Relevance
“…MicroRNAs (miRNAs) are a family of small single-stranded noncoding RNAs of approximately 19-24 nucleotides in length that have multiple functions in cancer, nervous development, metabolic disorders such as obesity, and cardiovascular diseases [ 5 ]. Mature miRNAs align and bind to the 3′-UTR sequences of their target mRNAs, and they are integrated into the RNA-induced silencing complex (RISC), leading to target mRNA degradation [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…MicroRNAs (miRNAs) are a family of small single-stranded noncoding RNAs of approximately 19-24 nucleotides in length that have multiple functions in cancer, nervous development, metabolic disorders such as obesity, and cardiovascular diseases [ 5 ]. Mature miRNAs align and bind to the 3′-UTR sequences of their target mRNAs, and they are integrated into the RNA-induced silencing complex (RISC), leading to target mRNA degradation [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Given the specificity of expression of lncRNAs, it would be careless to think that the dysregulation of the expression of these molecules in cardiac pathological processes, even if the molecular mechanism behind them is not exactly understood, was a mere coincidence [69]. The poor conservation of these interspecies transcripts, however, makes it difficult to translate findings in rodent models for human applications; however, several studies have shown promising results regarding the prognosis of CVDs and new therapies from the modulation of cardiac lncRNAs [33,34,70,89,90,172,173]. We summarize the lncRNAs and the CVDs (Figure 2).…”
Section: Lncrnas In Cardiovascular Diseasesmentioning
confidence: 99%
“…Considering all of the above regarding the regulatory role of lncRNAs in the cardiovascular system and the observation that the dysregulation of the expression of these transcripts has been observed in CVDs, it seems appropriate to consider them as molecular targets in therapies [173,[203][204][205]. Through counter-regulation, the restoration of physiological expression levels of lncRNAs can occur both through gain-of-function strategies (for those lncRNAs that are significantly impaired) and through loss-of-function strategies (for those overexpressed).…”
Section: Lncrnas As Biomarkers and Potential Therapeutic Targets For Cardiovascular Diseasesmentioning
confidence: 99%
“…They participate in many physiological and pathophysiological processes such as: the regulation of signaling platelet pathways, gene regulation of eukaryotes, angiogenesis, and insulin secretion [37][38][39][40]. MiRNAs are considered targets for personifying intervention and translational therapy [41]. Under pathological conditions, cells can usually passively or actively deliver mi-croRNAs into circulation.…”
Section: Mirnas Superfamilymentioning
confidence: 99%